2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8036811
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial stiffness does not respond to renal denervation in an animal model of secondary hypertension

Abstract: Renal denervation is a novel device based therapy promoted to reduce high blood pressure. We examined the impact of renal denervation on systolic blood pressure, renal function, and arterial stiffness in the Lewis Polycystic Kidney disease (LPK) rodent model of kidney disease. Animals were subjected to bilateral renal denervation or sham surgeries at age 6 and 12 weeks. Systolic blood pressure was monitored by tail-cuff plethysmography and renal function by urinalysis and creatinine clearance. At age 16 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As an earlier study from our group has demonstrated, chronic administration of the ACEi, perindopril to the LPK rat causes a reduction in the PWV index of arterial stiffness and enhances central artery compliance ( Ng et al, 2011 ). These results were not achieved by renal denervation of our animals ( Yao et al, 2017 ), and whether this is the case in different CKD animal models or humans with kidney diseases has not been fully investigated. Hence, further research in this area is required in order to establish a clear ground on the clinical outcome of RAS antagonism versus that of renal denervation.…”
Section: Pathogenesis Of Hypertension In Chronic Kidney Diseasementioning
confidence: 89%
See 2 more Smart Citations
“…As an earlier study from our group has demonstrated, chronic administration of the ACEi, perindopril to the LPK rat causes a reduction in the PWV index of arterial stiffness and enhances central artery compliance ( Ng et al, 2011 ). These results were not achieved by renal denervation of our animals ( Yao et al, 2017 ), and whether this is the case in different CKD animal models or humans with kidney diseases has not been fully investigated. Hence, further research in this area is required in order to establish a clear ground on the clinical outcome of RAS antagonism versus that of renal denervation.…”
Section: Pathogenesis Of Hypertension In Chronic Kidney Diseasementioning
confidence: 89%
“…Several trials have been conducted ( Krum et al, 2009 ; Investigators, 2010 ; Esler et al, 2012 ; Kandzari et al, 2012 ; Bakris et al, 2014 ; Bhatt et al, 2014 ; Liu et al, 2017 ; Sievert et al, 2017 ; Böhm et al, 2020 ), however to date, there is no global census or legislative approval of renal denervation as a clinical procedure for the treatment of hypertension non-pharmacologically. Although renal denervation has played an ameliorating role in reducing elevated BP and preserving renal function in diseased kidneys in humans ( Hering et al, 2012 ; Ott et al, 2015 ) and rats ( Yao et al, 2017 ) with CKD, other factors contributing to BP elevation remain, that are unalterable by renal denervation. For example, in our studies, we have shown that despite a reduction in BP and urinary protein of our CKD rat model, renal denervation did not fix the problem of increased arterial stiffness as assessed by pulse wave velocity (PWV), a hallmark of BP derived risk factor for morbidity ( Yao et al, 2017 ).…”
Section: Pathogenesis Of Hypertension In Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation